46,XY 5-ALPHA REDUCTASE 2 DEFICIENCY SYNDROME IN A 19-YEAR-OLD PHENOTYPIC FILIPINO FEMALE: A CASE REPORT - Hernandez , Hernessa; Paz-Pacheco, Elizabeth (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE Steroid 5 alpha-reductase 2 deficiency is a rare autosomal recessive disease caused by genetic mutation which results in the non-conversion of Testosterone to Dihydrotestosterone. The case is a nineteen-year-old, born from a none consanguineous marriage, reared as a female, who presented with primary amenorrhea. At the age of thirteen, she developed virilization with no development of secondary female sex characteristics. There were two palpable soft and non-tender inguinal masses measuring three centimeters. The external genitalia showed an acuminate pubic hair, a three-centimeter phallus-like structure, with fused labio-scrotal folds with ruggae, an empty scrotal sac, and a three-centimeter blind vaginal pouch where urine passes through. The testosterone level was at a normal level, with a testosteronedihydrotestosterone ratio of less than ten. The karyotype result revealed a male, 46,XY chromosome with no aberrations. The genetic analysis showed two pathogenetic variants of the SRD5A2 gene. After a multidisciplinary discussion, the patient adopted the male gender.